Recurrent Severe Hypoglycemia Secondary to Benign Phyllodes Tumour of the Breast : A Rare Case of Non-Islet Cell Tumor-induced Hypoglycemia (NICTH) - Tee, Hwee Ching; Valayatham, Vijiya Mala (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Non-Islet Cell Tumor-induced hypoglycemia (NICTH) secondary to phyllodes tumour is extremely rare but potentially life threatening if not treated promptly. We report a case of a 46-year-old female without underlying diabetes mellitus who presented with a large breast tumor and recurrent severe symptomatic hypoglycemia. Investigations supported the diagnosis of NICTH and the hypoglycemia only resolved after corticosteroids and mastectomy. This case highlights the importance of considering NICTH in the evaluation of patients with voluminous tumour and hypoglycemia.